Genetic and physiological characteristics of salt-tolerance in nine rice varieties at seedling stage - Nguyen Pham, Ngoc Diep; Le, Phuc Hau; Tran, In Do; Tong, Thi Thuy Trang; Pham, An Tinh; Huynh, Ky (Hue University Journal of Science: Natural Science, 2025)
Climate change has caused severe saltwater intrusion, significantly affecting rice production in the Mekong Delta. This study aims to evaluate the genotypes and salt tolerance of nine rice varieties, including two control varieties, FL478 (salt-tolerant) and IR29 (salt-sensitive), and seven other varieties: ST3, Lua Tim Can Tho, Lua Tim Vinh Long, ST24, Jasmine85, TNN91, and Vin16. The experiments were conducted under artificial conditions with zero and 100 mM NaCl in the Yoshida nutrient solution for 21 days. The genotypes were analysed with the 15 SSR primer pairs linked to salt-tolerance quantitative trait loci identified in FL478. The measured physiological parameters included Na⁺ and K⁺ ion contents in shoots and roots, the Na⁺-to-K⁺ ratio, and the proline content. The results reveal that 8 SSR primer pairs identified salt-tolerant genotypes similar to FL478. Physiologically, the salt-tolerant varieties maintained a low Na⁺-to-K⁺ ratio and efficiently accumulated proline, although FL478 accumulated less proline than IR29. This indicates that FL478 utilises proline more effectively for osmotic regulation and protecting cells from oxidative stress. The Membership Function Value of Salt Tolerance analysis grouped the 9 rice varieties into three categories according to their salt tolerance levels, with ST3 clustered in the highly salt-tolerant group alongside FL478. The study confirms the correlation between genotype and salt tolerance, providing a scientific basis for breeding rice varieties adapted to increasingly severe salinity conditions in the Mekong Delta.